The rising costs of nutritious foods in Ethiopia - Bachewe, Fantu Nisrane; Hirvonen, Kalle; Minten, Bart; Yimer, Feiruz (International Food Policy Research Institute, 2017)
Given the high prevalence of undernutrition among children in low income countries and the associated high human and eco-nomic costs (Hoddinott et al. 2013), improving nutritional out-comes must be an urgent priority. Improving nutrition is high on the policy agenda of the government of Ethiopia, as stated in the Growth and Transformation Plan II, which aims to reduce young child stunting levels from 40 percent in 2014/15 to 26 percent in 2019/2020. Lack of access to diverse diets is one of the underlying factors contributing to chronic undernutrition (Arimond and Ruel 2004, UNICEF 1998). Despite recent improvements, child stunting in Ethiopia remains widespread (CSA and ICF International 2017). Moreover, Ethiopian children consume one of the least diverse diets in sub-Saharan Africa (Hirvonen 2016). At the household level, food consumption baskets are dominated by cereals and pulses, while the consumption of animal-source foods and fruits and Vitamin A-rich vegetables is rare, especially in rural areas.1 Such monotonous diets are regarded as a major contributor to non-communicable diseases in Ethiopia (Melaku et al. 2016). Recent research suggests that the poor dietary diversity in ru-ral areas can be explained, at least partly, both by limited knowledge about the health benefits of diverse diets and by poor access to food markets. Households in areas in which food crop production is not very diverse but which have good access to mar-kets are found to have more diverse diets than do households in such areas but which have poor access to markets and, so, de-pend primarily on own-production for the food they consume.2 Yet, even with sufficient access to markets and knowledge on the benefits of diverse diets, poor households may simply be un-able to afford nutritionally rich foods (Warren and Frongillo 2017). Indeed, prices and affordability of nutritious foods remains a neglected area of research in efforts to understand poor dietary diversity in Ethiopia and elsewhere.3 In the analysis described here, we explore how prices and, consequently, the affordability of nutritious food have changed over the last decade in Ethiopia.